The age at first cutaneous manifestation of psoriasis as a prognostic factor in the timing of psoriatic arthritis diagnosis - Elena V. Bogdanova (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
Background. Psoriatic arthritis is a chronic inflammatory disease of joints, spine and enthesis, which develops in 640% of patients with psoriasis and has a significant impact on the quality of life of patients. Aims. To determine the relationship between age of cutaneous manifestation of psoriasis and the timing of psoriatic arthritis diagnosis; to examine the possibility of prediction of timing of psoriatic arthritis diagnosis depending on age of cutaneous manifestation of psoriasis. Materials and methods. Data of patients aged 18 years and older with psoriatic arthritis included in the psoriasis patient register were analysed. Inclusion criteria were: patient age 18 years and older; established diagnosis of psoriasis and psoriatic arthritis. Exclusion criteria were: psoriatic arthritis diagnosed before or simultaneously with cutaneous manifestation of psoriasis; the age of the cutaneous manifestation of psoriasis older than 70 years. The sample included 771 patients. Spearman's correlation analysis was used to assess the correlation between age of cutaneous manifestation of psoriasis and period from skin psoriasis onset to psoriatic arthritis diagnosis. The possibility of prediction of the period till psoriatic arthritis was diagnosed depending on age at cutaneous manifestation of psoriasis was established by means of quantile regression analysis. Results. Mean age at cutaneous manifestation of psoriasis (SD) was 26.0 13.5 years. The period from the onset of skin psoriasis to the diagnosis of psoriatic arthritis averaged 13.7 10.3 years, its median [interquartile range] was 12 [619] years. According to Spearman's correlation analysis, a moderate (close to strong) negative correlation between varibles was revealed (Spearman's correlation coefficient = 0.490, p 0.0005). In accordance to quantile regression analysis, lines of 5, 25, 50, 75 and 95% quantiles were obtained and the dependence of the period till the diagnosis of psoriatic arthritis on the age of onset of skin psoriasis was demonstrated. Based on the quantile equation obtained, a prognostic table for the period from the onset of skin psoriasis to the diagnosis of psoriatic arthritis was compiled. Conclusions. Statistically significant inverse relationship between age of cutaneous manifestation of psoriasis and period till psoriatic arthritis diagnosis was established: older age at skin psoriasis onset is associated with shorter period till psoriatic arthritis diagnosis. Based on established relationship, presented as an equation, table and graphically, prediction of period till psoriatic arthritis diagnosis is possible. These results can be used in the clinical practice of dermatovenereologists.